STRATEGI GURU KESISWAAN DALAM MENGHADAPI PERMASALAHAN PESERTA DIDIK DI SEKOLAH SMP HANJUANG - Febri Dahlia; Nur Azmi Wiantina; Fitri Husaibatul Khairat Hsb; Anida Khofiyah; Nila Wulandari; Laili Rizkiyah (Fakultas Tarbiyah dan Keguruan, 2025)
This student service and knowledge activity of the Faculty of Tarbiyah and Teacher Training aims to describe the role of Student Teacher Strategy in Facing Student Problems at National Plus Hanjuang Junior High School. The theory used in this study is interview theory, which allows researchers to dig deeper into information through direct communication with related parties. This study aims to identify and analyze the strategies of student teachers in dealing with the problems of students at SMP National Plus Hanjuang. Students' problems often include academic, disciplinary, and psychosocial aspects that affect the learning process and the development of their character. This study uses a qualitative approach with a case study method. Data was obtained through observation, in-depth interviews with student teachers and documentation related to school policies and programs. The results of the study showed that student teachers at SMP National Plus Hanjuang applied various strategies, such as individual coaching, a personal approach to students and parents, and the implementation of counseling guidance programs tailored to student needs. In addition, collaboration with external parties, such as psychologists and educational institutions, is also carried out to overcome more complex problems. The main challenges faced include limited resources, lack of support from parents, and high diversity of student problems. The conclusion of this study confirms that the role of student teachers is very vital in creating a school environment that supports the learning process. An effective strategy requires a holistic approach that involves students, teachers, and parents. This study recommends the development of a more structured model of strategies to address student problems at the junior high school level as a follow-up research agenda.